Cloning and expression of pab gene of M. tuberculosis isolated from pulmonary TB patient in E.coli DH5α (Medical Journal of Indonesia, 2011)
Background: Mycobacterium tuberculosis antigen38 is a potent serodiagnostic agent containing two M. tuberculosis specific B-cell epitopes. The high price of imported diagnostic agents hinders realization of fast clinical TB diagnosis in developing countries. Therefore, we produced recombinant antigen38 (recAg38M) from M. tuberculosis local strain, which might be used to produce economical tuberculosis serodiagnostic kit. Methods: Pab gene that was isolated from pulmonary TB patient in Malang was cloned into a plasmid vector (pGEMTeasy) to construct pMB38. The E.coli DH5α clone carrying pMb38 was selected on X-gal medium. The expression of pab was mediated using pPRoExHTc under the control of Trc promoter and E.coli DH5α as host. Results: Alignment of the pab sequence from the white E.coli DH5α clones with that of M. tuberculosis H37Rv showed 98% homology. The recombinant protein in which the signal peptide has been deleted to prevent the protein being secreted into medium was found in the cytoplasm. Conclusion: pab gene of M. tuberculosis isolated from a TB patient could be expressed in heterologous system in E.coliDH5α. (Med J Indones 2011; 20:247-54) Keywords: Mycobacterium tuberculosis, Pab gene expression, recombinant antigen38